To solve the equation \(4x - 4 = 2x + 8\), follow these steps:
-
Start by getting all terms involving \(x\) on one side and constant terms on the other side. We can do this by subtracting \(2x\) from both sides:
\[ 4x - 2x - 4 = 8 \]
This simplifies to:
\[ 2x - 4 = 8 \]
-
Next, add \(4\) to both sides to isolate the term with \(x\):
\[ 2x = 8 + 4 \]
This simplifies to:
\[ 2x = 12 \]
-
Now, divide both sides by \(2\) to solve for \(x\):
\[ x = \frac{12}{2} \]
Which simplifies to:
\[ x = 6 \]
So, the solution to the equation \(4x - 4 = 2x + 8\) is \(x = 6\).